Inter-individual response differences on resting blood pressure as a result of qigong in adults: An ancillary meta-analysis of randomized trials - George A. Kelley; Kristi S. Kelley; Brian L. Stauffer (Elsevier, 2022)
Objective: Conduct an ancillary meta-analysis to determine whether true inter-individual response differences (IIRD) exist with respect to the effects of qigong on resting systolic blood pressure (SBP) and diastolic blood pressure (DBP) in adults. Methods: Data from a meta-analysis representing 370 participants (181 qigong, 189 control) from 7 randomized trials on qigong and resting SBP and DBP in men and women were included. Qigong and control group change outcome standard deviations treated as point estimates for both resting SBP and DBP were used to calculate true IIRD from each study. The inverse variance heterogeneity (IVhet) model was used to pool results. Results: For participants with essential hypertension, statistically significant and clinically important reductions in resting SBP (X̅, −18.2 mmHg, 95% CI, −21.3 to −15.2 mmHg) and DBP (X̅, −11.7 mmHg, 95% CI, −17.0 to −6.3 mmHg) were found. However, true IIRD were neither significant nor clinically important for either SBP (X̅, −6.0 mmHg, 95% CI, −9.1 to 3.5 mmHg) or DBP (X̅, 2.8 mmHg, 95% CI, −3.4 to 5.2 mmHg). The 95% prediction interval for true IIRD was − 11.9 to 8.4 mmHg for SBP and − 5.8 to 7.0 mmHg for DBP. Conclusions: While qigong is associated with reductions in resting SBP and DBP in adults with essential hypertension, a lack of true IIRD exists, suggesting that other external factors are responsible for any variation.